PENGARUH INISIASI MENYUSU DINI TERHADAP INVOLUSI UTERUS PADA IBU POSTPARTUM - Desideria Yosepha Ginting; Syafria Nirwana; Arfah May Sara; Layari Tarigan (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Early Breastfeeding Initiation is the process of breastfeeding babies as soon as they are born and can not be postponed by weighing or measuring the baby. The purpose of this study was to determine the effect of Early Breastfeeding Initiation on uterine involution in postpartum mothers. This type of research is Quarsi Experimental Design with observation research. the population in this study were all postpartum mothers at Tutun Sehati Tanjung Morawa’s Clinic Deli Serdang Regency. Samples taken amounted to 10 people, used with observation techniques, which were divided into two groups, namely control (which was not given Early Breastfeeding Initiation) and intervention (given IMD).The result that the average Uterine Revolution in postpartum mothers who were controlled was 11.40 with a standard deviation of 0.54.while the intervention group performed by Early Breastfeeding Initiation was 9.20 with a standard deviation of 0.47. so there is an effect of Early Breastfeeding Initiation on uterine involution in postpartum mothers with a p-value = 0.003 (P <0.05), It is recommended that health workers do Early Breastfeeding Initiation to postpartum mothers to accelerate the decrease in uterine involution.